Legal Arrangement Model for Imposing Fair Interest on Online Loans - Nurhilmiyah Nurhilmiyah; Hazmi Rusli; Destri Budi Nugraheni; Atikah Rahmi; Ismail Koto (Kosmik Hukum, 2026)
The issue of the amount of interest on online loans or peer-to-peer lending has become an actual issue and raises problems from the aspect of legal protection for the parties. Reasonable and fair interest for parties can expand financial access and increase the achievement of financial inclusion of the Indonesia people. This study uses normative legal research methods but is equipped with supporting data from observations and interviews from the field as using empirical legal research methods. Based on the discussion carried out it can be seen that the information contained in the online loan application is not transparent regarding the existence of reasonable interest rates on online loans, does not provide legal certainty for consumers, especially in protecting their rights, this is due to the fact that there are still many business actors who provide unclear information. The legal regulation model for the imposition of fair interest on co-financing services or online loan services since the issuance of the Financial Services Authority Circular No 19/SEOJK.06/2023 concerning the Implementation of Information Technology-Based Co-Financing Services the interest is expressly differentiated between productive funding and consumptive funding